Sativene Sesquiterpenoids from the Plant Endophytic Fungus Bipolaris victoriae S27 and Their Potential as Plant-Growth Regulators - Wang, Xin-Jia; Wang, Zhe; Han, Jing; Su, Shi-Huang; Gong, Yuan-Xiang; Zhang, Yu; Tan, Ning-Hua; Wang, Jia; Feng, Li (Journal of agricultural and food chemistry, 2024)
Thirteen new sativene sesquiterpenoids (1 and 3–14), one new natural product (2), and 16 known compounds (15–30) were isolated from the endophytic fungus Bipolaris victoriae S27. Their structures were elucidated by extensive spectroscopic analysis, NMR and ECD calculations, and X-ray crystal diffractions. Compound 1 represented the first example of sativene sesquiterpenoids with a 6/5/3/5-caged tetracyclic ring system. All obtained compounds were evaluated for their plant-growth regulatory activity. The results showed that 1, 3, 4, 6, 8, 11, 12, 17, 19, 26, and 27 could suppress the growth of Arabidopsis thaliana, while 2, 5, 13, 15, 18, and 25 showed promoting effects. Among them, compound 3 showed the most potent plant-growth inhibitory activity, which is obviously superior to that of the marked herbicide glyphosate.